Meaning, Morals and the Existence of God - McCarthy, Gerald (Horizons, 1982)
This essay is divided into two sections. Part I analyzes and compares in detail the arguments of Schubert Ogden and Hans Küng for the existence of God. Essentially, both Küng and Ogden argue that certain characteristic human activities (especially moral choices) presuppose a confidence (Ogden) or a basic trust (Küng) that our lives and reality of which our lives are a part are meaningful. They continue to argue that this confidence or this basic trust are only justifiable on the condition of belief in God. Hence, they conclude that a belief in God is presupposed by our moral choices. Part II critically evaluates the above argument by drawing on distinctions made by analytic philosophers (Baier, Nielsen, Ayer) in their discussions of what conditions are necessary and sufficient to make a life (or life) meaningful. The discussion with analytic philosophy is important because neither Küng nor Ogden take any notice of the arguments raised there.